Reading against the grain of vulnerability in addiction: Philosophical reflections on agency and vulnerability - Uusitalo S. (the Finnish Anthropological Society, 2022)
Addicted individuals are arguably a vulnerable population in health care and in society. Typically, the claim is based on views that consider drug use as the source of vulnerability, either as a cause for pathologies in the brain or as a target for societal regulation that results in harm for the users. In this article, I question the common conceptions that, first, the vulnerability in addiction actually traces back to drug use and, second, vulnerability in addiction undermines the addicted individual’s agency. Insofar as drug use is considered to be the main source of vulnerability in addiction, the view of addicted individuals as vulnerable may be misplaced. I suggest that in certain contexts drug use can be regarded as a resource in one’s agency. However, questioning the polarization between autonomy (i.e., full-blown agency) and vulnerability may undermine the view that addicted individuals are a vulnerable population that requires special measures.